Retrofitting and Investigation of Performance of Box Girder Bridge Using Glass Fiber Reinforced Polymer (GFRP) - Alami F; Lanoe S J; Isneini M (International Conference on Engineering and Technology Development (ICETD), 2017)
Namosain box-girder bridge was located in Kupang City at Province of Nusa Tenggara Timur (NTT). This bridge was built in 2008 and recently suffered any cracks on the bottom of slab of the box girder during its service load. This bridge was retrofitted using Glass Fiber Reinforced Polymer (GFRP) to reinstate and improve its performance against live loading. Two layers of GFRP, one in longitudinal direction and another in transverse direction was bonded on the bottom of box girder using epoxy resin. The stiffness of the bridge was improved significantly by evaluating its deflection before and after strengthening. Static loading test by using truck loading was performed after 30 days of retrofitting. Stiffness of the bridge was increased by 45% to 70%